Functionality of Family in Modern Transitive Society - A. D. Andreyeva (Научный диалог)
The article presents a review of psychological and sociological studies of the family in modern transitive society that allows to analyze various factors determining its ability to execute major social functions. Socio-cultural analysis of modern society is based on the concept by M. Mead on the types of culture of human society, determined by the pace of change of material and social living conditions. Under this approach the prefigurative type of social culture is seen as dominant at the turn of 20th-21st centuries. Basic settings of family functionality are revealed, retaining its relevance and effectiveness in a new environment. It is proved that modernization of the modern family consists in decreasing its composition, weakening of child-centrism, depreciation of the experience of parental practices of previous generations, attitudes of young parents on the expert opinion of the Internet community. The pathogenic factors of the current social environment are the expansion of physical space of life, the complexity of social infrastructure, occupation of adult members of the family, man’s information overload, the emergence of new communication environment and weakening of parental control over this area of social interaction of children. Practical value of research is determined by the possibility to use its results in educational practices and organization of family consultation.